2015
DOI: 10.1111/bjc.12096
|View full text |Cite
|
Sign up to set email alerts
|

Future‐directed thinking in first‐episode psychosis

Abstract: ObjectivesThis study employed the Future Thinking Task (MacLeod et al., 2005, Br. J. Clin. Psychol., 44, 495) to investigate whether future‐directed thinking in first‐episode psychosis is significantly different from that of matched controls, and to identify its correlates in this patient group.DesignCross‐sectional, mixed‐model, case–control design.MethodParticipants were 30 patients with first‐episode psychosis and 27 matched controls. The Future Thinking Task was used to assess future‐directed thinking in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 170 publications
4
9
0
Order By: Relevance
“…One might have expected the schizophrenia group to show greater difficulties for hypothetical, distant rewards in light impaired abstract thinking and longer-term prospection associated with this disorder (Eack & Keshavan, 2008; Fioravanti, Carlone, Vitale, Cinti, & Clare, 2005; Goodby & MacLeod, 2016). However, the pattern found in the current study may relate to participant and task characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…One might have expected the schizophrenia group to show greater difficulties for hypothetical, distant rewards in light impaired abstract thinking and longer-term prospection associated with this disorder (Eack & Keshavan, 2008; Fioravanti, Carlone, Vitale, Cinti, & Clare, 2005; Goodby & MacLeod, 2016). However, the pattern found in the current study may relate to participant and task characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, it remains unclear whether people with psychotic symptoms or schizophrenia, compared to healthy controls without psychiatric diagnoses, have difficulty generating positive and negative future events (Goodby & MacLeod, ; Raffard, Esposito, Boulenger, & Van der Linden, ) or whether the deficit is specific to positive events (Chen et al ., ). Also, although future thinking impairments may be explained by impairments in autobiographical memory (Kwan, Carson, Addis, & Rosenbaum, ; Schacter, Addis, & Buckner, ), studies of schizophrenia have shown mixed findings regarding the association between past and future thinking abilities, or have not reported correlations specifically within the clinical group, instead conflating them with diagnoses‐free control participants (Chen et al ., ; D'Argembeau, Raffard, & Van der Linden, ).…”
Section: Introductionmentioning
confidence: 99%
“…One reason for the discrepancyies between previous studies could be that participants generate fewer future events unless explicitly asked to generate as many as possible, resulting in insufficient between‐participant variability to examine group differences. Goodby and MacLeod () overcame this limitation by asking participants who had experienced positive symptoms of psychosis (e.g., delusion, hallucinations) within the last 12 months to generate as many positive and negative events (events they are looking forward to or are not looking forward to) as possible within 3 min for each valence. These participants showed an impaired ability to generate both positive and negative events compared to controls (Goodby & MacLeod, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations